The mechanism for H2S scavenging by 1, 3, 5-hexahydrotriazines explored by DFT. Issue 16 (17th April 2020) - Fiorot, Rodolfo G.; de M. Carneiro, José Walkimar
Abstract: Hydrogen sulfide, H2 S, stand as one of the major issues in petroleum industry. Aqueous solutions of triazines are the most utilized non-regenerative H2 S scavenger. Although they present a theoretical capture capacity of 3 mol of H2 S per mole of triazine, it effectively scavenges only 2 mol. Herein, we employed Density Functional Theory at CAM-B3LYP/6–311++G(2d, 2p) level of calculation to rationalize the full mechanism for capture of H2 S by hexahydro-1, 3, 5-triazines, in particular the reason why the reaction stops at the second equivalent of H2 S. For the capture of the first equivalent of H2 S, we found an unprecedented SN 1 pathway to be less energetic than SN 2, the most commonly accepted in literature. For capture of a second H2 S molecule, however, both mechanisms are energetically similar. High barriers were found for the capture of the third molecule of H2 S, related to the lower electrophilicity of the carbon atom bonded to nitrogen and sulfur atoms. Graphical abstract: Image 1 Highlights: The mechanism for H2 S scavenging by triazines depends on the substitution at the electrophilic carbon. Carbon atoms connected to a sulfur atom are less electrophilic than those connected to nitrogen. The capture of the first equivalent of H2 S by 1, 3, 5-hexahydrotriazines occurs via a SN 1 mechanism. For capture of the second H2 S molecule SN 1 and SN 2 mechanisms are competitive. After capturing the second H2 S molecule the barrier for further H2 S scavenging becomes prohibitive.